GAMBARAN PENGETAHUAN PASIEN TUBERCULOSIS PARU TENTANG PUTUS OAT (OBAT ANTI TUBERCULOSIS) DI RSU IPI MEDAN TAHUN 2019 - Jenti Sitorus (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Pulmonary tuberculosis is an infectious disease that attacks the lungs which is typically characterized by the formation of granulomas causing tissue neocrosis. Pulmonary tuberculosis is caused by "mycrobacterium tuberculosis" a type of rod-shaped germ with a length of 1-4 / mm and a thickness of 0.3 -0.6 / mm. The World Health Organization (WHO) in 2007 stated that the number of tuberculosis sufferers in Indonesia was around 528 thousand or in third place in the world after India and China. The WHO report in 2009 recorded Indonesia's ranking according to fifth position with the number of tuberculosis sufferers of 429 thousand people, namely India, China, South Africa, Nigeria, and Indonesia (source WHO Global Tuberculosis Control 2010). This study aims to describe the knowledge of pulmonary tuberculosis patients about anti-tuberculosis drug withdrawal at RSU IPI Medan who is experiencing pulmonary tuberculosis. The sampling technique used in this research is Probability Sampling with the Random Sampling technique. Then the number of samples is 40 respondents. researchers used primary data. With the results of the study, it is hoped that respondents will increase their knowledge by finding out and caring about the health of others in order to prevent the transmission of pulmonary tuberculosis and change bad behavior for the better, with the participation and cooperation of medical personnel and other health teams in provide precise and accurate information.